Recombination Lifetime Measurements in Silicon 1998
DOI: 10.1520/stp15700s
|View full text |Cite
|
Sign up to set email alerts
|

Present Status of the Surface Photovoltage Method (SPV) for Measuring Minority Carrier Diffusion Length and Related Parameters

Abstract: We present an overview of the physics and practical issues related to surface photovoltage measurement of the minority carrier diffusion length and its application to monitoring recombination center defects in silicon. A tutorial description is given of the role of pertinent processes like injection, recombination and trapping. The evolution of the SPV method is presented followed by a description of most recent refinements addressing the measurement of long diffusion lengths in silicon wafers with emphasis on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…More recently, Faifer et al [538] have examined the relation between the spot and electrode size in scanning systems and concluded that the latter should be bigger than the former by at least one diffusion length on either side in order to reduce errors due to lateral diffusion effects. This point was further investigated by Lagowski et al [530]. They concluded that when the electrode and spot size are essentially the same, as in Fig.…”
Section: Limitations and Solutionsmentioning
confidence: 86%
See 4 more Smart Citations
“…More recently, Faifer et al [538] have examined the relation between the spot and electrode size in scanning systems and concluded that the latter should be bigger than the former by at least one diffusion length on either side in order to reduce errors due to lateral diffusion effects. This point was further investigated by Lagowski et al [530]. They concluded that when the electrode and spot size are essentially the same, as in Fig.…”
Section: Limitations and Solutionsmentioning
confidence: 86%
“…Sopori et al [537] noted relatively early on that the spot size must be large enough to avoid lateral diffusion effects. They predicted that lateral diffusion would be negligible and the true value of L obtained only if the spot size is at least 30 times as wide as L. In view of the results of, e.g., Lile [427] and Lagowski et al [12,529], this quantitative criterion seems to be much too harsh. Nevertheless, the qualitative conclusion is correct.…”
Section: Limitations and Solutionsmentioning
confidence: 99%
See 3 more Smart Citations